Creatinine, leucine, and tetrahydrocorticosterone emerge as potential biomarkers for the diagnosis of sarcopenic osteoarthritis in middle-aged and elderly individuals: a cross-sectional exploratory study - Wu, Huihui; Gao, Hui; Guo, Liang; Feng, Xinyu; Zhang, Zhishen; Zhao, Yiding; Chen, Haihong; Wang, Zhi (Frontiers in Molecular Biosciences, 2026)
BackgroundOsteoarthritis is a common degenerative joint disease that is often associated with age-related muscle wasting known as sarcopenia, particularly in the elderly. This comorbid condition, referred to as “sarcopenic osteoarthritis”, may have a distinct metabolic profile; however, specific serum biomarkers for this phenotype remain poorly characterized. Therefore, we conducted an untargeted serum metabolomics study to identify potential biomarkers of osteoarthritis in individuals with sarcopenia.MethodsThis cross-sectional study enrolled 82 participants categorized into healthy controls, osteoarthritis, and sarcopenic osteoarthritis groups (n = 30, 30, 22). Fasting serum was analysed by untargeted LC-MS metabolomics. Differential metabolites were identified using multivariate statistics (PCA, PLS-DA; VIP >1) combined with univariate tests (P < 0.05, FDR-adjusted q < 0.05, |log2FC| ≥ 1). Enriched KEGG pathways were determined (P < 0.05).ResultsMetabolomic analyses distinguished sarcopenic osteoarthritis from osteoarthritis alone by significant alterations in steroid hormone biosynthesis and sphingolipid metabolism. We screened a total of 20 substances for use as biomarkers of sarcopenic osteoarthritis and ended up focusing mainly on three of them.ConclusionUntargeted serum metabolomics successfully distinguished between healthy controls, osteoarthritis, and sarcopenic osteoarthritis and identified several candidate biomarkers. Creatinine, leucine, and tetrahydrocorticosterone emerged as promising biomarkers for the detection and phenotyping of the distinct sarcopenic osteoarthritis phenotype based on their clinical relevance and ease of measurement.